Global increase in methane production under future warming of lake bottom waters. (24th June 2022) - Jansen, Joachim; Woolway, Richard Iestyn; Kraemer, Benjamin M.; Albergel, Clément; Bastviken, David; Weyhenmeyer, Gesa A.; Marcé, Rafael; Sharma, Sapna; Sobek, Sebastian; Tranvik, Lars J.; Perroud, Marjorie; Golub, Malgorzata; et al.
Abstract: Lakes are significant emitters of methane to the atmosphere, and thus are important components of the global methane budget. Methane is typically produced in lake sediments, with the rate of methane production being strongly temperature dependent. Local and regional studies highlight the risk of increasing methane production under future climate change, but a global estimate is not currently available. Here, we project changes in global lake bottom temperatures and sediment methane production rates from 1901 to 2099. By the end of the 21st century, lake bottom temperatures are projected to increase globally, by an average of 0.86–2.60°C under Representative Concentration Pathways (RCPs) 2.6–8.5, with greater warming projected at lower latitudes. This future warming of bottom waters will likely result in an increase in methane production rates of 13%–40% by the end of the century, with many low‐latitude lakes experiencing an increase of up to 17 times the historical (1970–1999) global average under RCP 8.5. The projected increase in methane production will likely lead to higher emissions from lakes, although the exact magnitude of the emission increase requires more detailed regional studies. Abstract : Projected changes in global lake bottom water temperatures (top) drive future increases in methanogenesis rates (bottom) under different climate warming scenarios (RCPs) by the end of the 21st century. Global lake temperature simulations of the ISIMIP2b Lake Sector (1901 to 2099), were combined with an Arrhenius‐type temperature function of methanogenesis derived from lake sediment incubations. While bottom water warming in northern lakes is muted by increased water column stratification, greater warming of lake bottom waters in the tropics, combined with increased temperature sensitivity of methanogenesis at higher temperatures suggest that tropical lakes will experience the largest increases in methane production.